Personality type as a determinant of help-seeking behaviour - Goh, Chew Meng. (2008)
This research study was mooted as a result of the government's efforts to introduce a wider scope of pupil welfare programmes through the school's Pastoral Care and Career Guidance (PCCG) department. In order to combat the ill effects of rising divorce rates, juvenile delinquency and attempted suicides, school-based counselling has been introduced as one of the many initiatives to strengthen family ties, and provide support services to people who need it.